Non-communicable chronic diseases: Mortality of older adult citizens in Brazil and Italy before the Covid-19 pandemic - Vicente Paulo Alves; Regina Célia de Oliveira; Dario Gregori (Elsevier, 2021)
The purpose of this study was to outline the main non-communicable chronic diseases that led older people to death in Brazil and Italy before the SARS-CoV-2 pandemic according to age gaps and region of residence. This study has identified that the highest mortality rate among Brazilian and Italian women took place in lower-income areas, potentially due to insufficient public policies to increase income and improve health, which would in turn reduce the risk of chronic diseases and increase life expectancy. Men showed higher mortality rates in different regions, and tended to die earlier. Our results highlight socioeconomic differences in the areas with the highest death rates due to non-communicable chronic diseases, emphasizing the relevance of public policies to meet the needs of the overall population.